INTRODUCTION OF DEMO3D INTO THE SCIENTIFIC EDUCATION OF MATERIAL HANDLING - Telek, Péter; Trummer, Wolfgang (Advanced Logistic Systems - Theory and Practice, 2019)
Using of advanced machines and methods requires highly educated engineers, who gain their basic knowledge at universities. In the aspect of material handling, the Institute of Logistics of the University of Miskolc (LOG) is one of the leading education centres in Hungary, so its teaching materials, methods and devices have significant effects to the knowledge of future logistic engineers. In this paper, we describe the state of the art of planning of material handling and the education structure of LOG. Main objective of this paper is to present developing possibilities of the scientific education of LOG with some help of the Institute of Engineering Logistics of TU Graz (ITL) in the frame of project UMi-TWINN. One of the most important results of the project is the application of the Demo3D software for the education of material handling. The developed examples, videos, sheets and other documentations are directly usable in the teaching curricula of different courses of LOG.